(untitled) (Journal of the College of Basic Education, 2026)
The potential and possibility of globally transforming the functions of teaching and learning can come from the incorporation of artificial intelligence into higher education. Nevertheless, in Iraqi contexts, this process is still in its initial stages, facing multifaceted implementation challenges. This study aims to address a central research problem: identifying the primary obstacles that hinder the effective integration of AI in Iraqi higher education, particularly from socio-cultural, institutional, and technical perspectives. Although only a limited number of implementation variables were analyzed, the study provides a foundational step toward understanding broader systemic barriers. In response to this problem, the study employs a mixed-methods approach to explore the perceptions of faculty and administrators, guided by an implicit hypothesis that institutional and infrastructural limitations significantly influence the adoption of AI. Furthermore, while a validated instrument was not initially discussed in detail, the research process included key reliability and ethical considerations to ensure data integrity. Iraq stands at a critical crossroads where artificial intelligence can enable it to bypass outdated pedagogical models and transition into globally competitive educational standards. AI offers a strategic solution to systemic issues like low educational quality, insufficient resources, and outdated curricula. Through practical mechanisms and policy reform suggestions, the study ultimately presents a roadmap for AI integration that promotes inclusive learning and skill development, thereby fostering Iraq’s social and economic growth.